Body mass index and outcomes of endometrial and ovarian cancer patients. Issue 3 (3rd May 2016) - Smits, Anke; Lopes, Alberto; Bekkers, Ruud; Massuger, Leon; Galaal, Khadra
ABSTRACT: Endometrial cancer and ovarian cancer are the most common gynaecological cancers in the developed world and are known to be associated with obesity. The escalating obesity epidemic in countries such as the United Kingdom has resulted in the majority of these patients being overweight or obese. Despite studies reporting on adverse effects of obesity throughout endometrial and ovarian cancer treatment and survivorship, a comprehensive overview is still unavailable. Given the fact gynaecological oncologists increasingly treat women within the obese, morbidly obese and even super obese classifications, it is essential to develop appropriate guidelines for clinical care. Through an analysis of the existing literature, we present a review of the current knowledge of the effect of body mass index on outcomes of endometrial and ovarian cancer patients, including treatment outcomes, quality of life and survival.